Linking gut microbiota to cardiovascular disease and hypertension: Lessons from chronic kidney disease. (July 2018) - Meijers, B.; Jouret, F.; Evenepoel, P.
Graphical abstract: Abstract: Bidirectional interactions exist between the kidneys and the gut. These interactions are commonly referred to as the gut-kidney axis. Chronic kidney disease (CKD) leads to disturbances of the gut ecosystem. Key features include the increase of protein fermentation at the expense of carbohydrate fermentation and a disrupted epithelial barrier. A disturbed gut ecosystem may contribute to the high burden of cardiovascular disease in patients with CKD. The present review discusses the impact of CKD on the gut microenvironment and provides an update as to how gut dysbiosis and a leaky gut may be linked to accelerated cardiovascular disease and hypertension.